Ursus maritimus - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2009)
8. Polar Bear Ursus maritimus French: Ours blanc / German: Eisbar / Spanish: Oso polar Other common names: \White Bear, Nanook Taxonomy. Ursus maritimus Phipps, 1774, Spitsbergen, (Svalbard) Norway. Considered a sister species to U. arctos. Most closely related to Brown Bears on the Admiralty, Baranof, Chichagof islands of south-east Alaska. Although several distinct populations or stocks have been delineated, small genetic differences have been found among these, and no subspecies have been differentiated. Monotypic. Distribution. Arctic Ocean: Canada, USA (Alaska), Greenland, Norway (Svalbard), Russia. Have been sighted within 0-5° of North Pole. Descriptive notes. Head-body 180-280 cm, shoulder height up to 170 cm,tail 6-13 cm; adult males are about twice as heavy (300-650 kg, but up to 800 kg) as adult females (150-250 kg, but up to 500 kg when pregnant), making them one of the most sexuallydimorphic mammals. Size varies regionally, being smallest in eastern Greenland, and progressively larger westward to the Bering Sea. Facial profile is straight, the neck is longer than in other bears, and the ears are small in relation to head and body size. Coat color appears white or yellowish, with no other markings, but can accumulate colors from the environment (e.g. blood and oils from killed prey). In reality, both guard hairs and underfur are translucent, and guard hairs are hollow, thus enhancing their insulation properties. However, a previous assertion that they act as fiber optic tubes, funneling sunlight to the skin for warmth, has been disproven. The skin is black, but only the black nose is visible. Summer coats are shorter than winter coats, but unlike other bears, coat thickness is not sparser ventrally. Additionally, the paws are well-furred on the underside, and have small soft papillae and vacuoles that may act as suction cups for traction on ice. The feet are also relatively large, providing more surface area for swimming and walking on thin ice. The claws are shorter and more curved than Brown Bears, and are usually dark-colored. Habitat. Arctic ice provides a necessary platform for hunting seals. Annual ice adjacent to coastlines (shore fast ice) regularly fractures, providing open leads where seals can breathe. The seasonal fluctuations between freezing and open water also promotes high productivity of fish, the prey of seals. Thus, this habitat is preferred by seals, and is consequently a favored habitat for Polar Bears, which hunt seals along the ice cracks and edges. Polar Bears also hunt from large chunks of drifting ice, and to a lesser extent, multiannual pack ice, where seal density is lower and access to seals more difficult. For this reason, density of Polar Bearsis low close to the North Pole. In summer, when the ice retreats, bears either migrate northward or use nearshore terrestrial habitats. Parturient females stay ashore to den and give birth. In Hudson Bay (Canada) they den 10-80 km inland in peat banks; elsewhere maternity dens are typically in snow caves along coastal areas. However, in the Beaufort Sea, half the pregnant females den on drifting sea ice. Non-pregnant bears do not hibernate, but do use shelter dens. At lower latitudes, they use shelters on land during ice-free periods to escape heat and conserve energy when precluded from hunting seals; at high latitudes (above 75° N) they seek shelters on thick sea ice during winter, when foraging is most difficult and weather conditions harshest. Food and Feeding. Almoststrictly carnivorous, preying mainly on young Ringed Seals (Pusa hispida), to a lesser extent Bearded Seals (Erignathus barbatus), and in some areas, Harp Seals (Pagophilus groenlandicus). The principal focus on Ringed Seals is evident in the close association between Polar Bear density and Ringed Seal density, and in the unique behavior of these seals, which give birth in subnivian lairs as an anti-predation strategy. One study found that an average Polar Bear consumes fewer than 50 Ringed Seals a year, 80% being pups caught either in their lairs or shortly after emerging from their lairs. Polar Bears also occasionally prey on other marine mammals, such as Walruses (Odobenus rosmarus), and Beluga (Delphinapterus leucas) whales. These large prey, including Bearded Seals (which are much larger than Ringed Seals), are taken mainly by adult male bears. When ashore, depending on availability, Polar Bears have been observed to prey on Reindeer (Rangifer tarandus), seabirds, or fish; and eat carrion (dead whales), berries, vegetation, and human garbage. Activity patterns. Appear to be mainly diurnal. Seasonal changes in activity vary regionally with dynamics of sea ice and abundance of prey. Activity, measured by percent of time active and distance moved,is elevated when seal pups are particularly naive and vulnerable to predation, and when older seals are molting and basking on the ice. In contrast to other predators, Polar Bears are most active when prey is most abundant. They become hyperphagic, and are able to store fat to withstand extended periods when foraging is more difficult, such as during the winter on the pack ice. Periods of rapid annual ice formation and ablation, during summer and fall, also result in greater activity. Parturient females den for about six months (mid-September to mid-March in most areas); non-pregnant Polar Bears do not hibernate. Movements, Home range and Social organization. Although once thought to wander aimlessly or be carried passively on shifting ice, recent data collected using satellite radio collars have shown that Polar Bears have definite home ranges that are used year to year. However, these ranges can be enormous: one female bear traveled over 5200 km from Alaska to Greenland in four months. Nevertheless, most bears seem to remain within a discrete population, or stock; 19 or 20 such populations have been identified across the geographic range. Home ranges and movements are highly variable by region, habitat, season, and reproductive condition or family association. Around Svalbard, nearshore bears tend to have smaller home ranges than pelagic bears. In the Canadian Arctic, bears that live in areas with highly variable and unpredictable ice conditions (including ice-free periods) have larger ranges than bears living on more stable ice. Individual ranges as large as 600,000 km * have been reported, but so have ranges of less than 1000 km ®. Means among different populations range from 20,000-250,000 km?. Little movement data have been collected on males, because they cannot be radio-collared (their necks are bigger than their heads), but data from implanted transmitters indicate that, unlike terrestrial bears, their ranges are not larger than those of females. With females being so mobile, and having highly overlapping ranges, males can include multiple potential breeding partners within their range, even if their range is not larger than the females’. Female maternity dens are highly congregated in some areas, such as Wrangel Island, parts of Svalbard, Franz Josef Land, Novaya Zemlya, and near Churchill, Manitoba. Breeding. Breeding occurs from March to June. Mating induces ovulation, and males spar for mating partners. Implantation of the fertilized egg is delayed until autumn, about the time that females enter maternity dens. In some areas this follows a period of on-shore fasting, so by the time these mothers emerge from dens the following spring they may not have eaten for eight months. Birthing occurs mid-November to January, so the total gestation, including the period of delayed implantation, is from 6:5 to more than 8-5 months. Cubs stay in the den until March or early April. Two-cublitters are most common, and average litter size is less than two in virtually all populations; however, litters of three are not uncommon in some areas, and litters of four have been reported. Females have only four mammae (other bears, except Sun Bears and Giant Pandas have six), so this is the maximum litter size. Average age offirst birthing ranges among different populations from 4-6-7-2 years. Productivity increases into the teen years, but then declines through the early 20s, and ceases by the late 20s. Intervals between litters average 2-1-3-6 years. Cubs separate from their mother either at 17 months, or more commonly a year later. Cubs may nurse through their second birthday. The fat content of milk is very high initially (more than 30%), but declines through the nursing period. Status and Conservation. CITES Appendix II. In 2006 The IUCN Red List status was upgraded to Vulnerable due to projections of dramatic reductions in habitat (coverage and stability of the ice sheet) over the next 50-100 years. Demographic consequences to Polar Bears are already becoming apparent in some areas, in terms of reduced numbers and reduced survival ofjuveniles and old adults. Ringed Seals are also suffering increased mortality from Polar Bear predation because of melting of their subnivian dens. Accordingly, the USA listed the species as nationally threatened and Canada listed it as a species of special concern. This would impose further constraints on activities that affect these bears or their habitat, such as hunting, recreational viewing, shipping, and oil and gas exploration and development. The effects of sea ice change will vary enormously by region, which is difficult to forecast, but overall arelikely to be dramatic and permanent. Nineteen fairly discrete populations have been identified, with a total world population estimated at 20,000-25,000; about half this number resides in the Canadian territory of Nunavut. Under an agreement for co-management of Polar Bear populations that was ratified in 1976, the five range countries coordinate and consult with each other on research activities, methods of population estimation and monitoring, and proposals for increased protection. Most importantly, under this treaty, harvestis restricted: the taking of cubs or females with cubs is prohibited, and harvest is limited to native people for subsistence use. This includes consumption of meat, use of hides for clothing, and creation of handicrafts. In some territories of Canada, a portion of the annual harvest is allocated to non-native sport hunters who employ native guides and hunt using dogsleds and other traditional methods. This generates income for the native communities. Harvests are regulated to be sustainable. Recently, pressure has mounted to reduce or prohibit harvests so as not to compound the effects of diminishing sea ice habitat from global warming. Bibliography. Amstrup (2003), Amstrup & Gardner (1994), Amstrup et al. (2001), Bentzen et al. (2007), Derocher (1999), Derocher, Andersen & Wiig (2005), Derocher, Andriashek & Stirling (1993), Derocher, Wiig & Anderson (2002), Durner & Amstrup (1995), Ferguson, Taylor, Born et al. (1999), Ferguson, Taylor, Rosing-Asvid et al. (2000), Garshelis (2004), Linnell et al. (2000), Mauritzen et al. (2001), Messier et al. (1992, 1994), Paetkau et al. (1999), Parks et al. (2006), Ramsay & Stirling (1990), Regehr et al. (2007), Rosing-Asvid (2006), Schliebe et al. (2006), Shields et al. (2000), Stirling (1988, 2002), Stirling & Jritsland (1995), Stirling & Parkinson (2006), Taylor et al. (2001), Thiemann et al. (2007). : Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Ursidae, pp. 448-497 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on pages 496-497, DOI: 10.5281/zenodo.5714493